Una singola definizione di lusso? Verso una lussuologia (Itinera, 2025)
A single definition of luxury? Towards a luxury studiesLuxury is often described as a pervasive phenomenon across societies and is inherently linked to various forms of inequality. However, a universally accepted definition remains elusive, largely due to the limited attention philosophy has devoted to the subject. Despite this, numerous renowned philosophers have addressed luxury, either directly or through evaluations of its intrinsic characteristics. This paper aims to propose more than three definitions of luxury, each particularly relevant within a specific domain: moral philosophy, aesthetics, and economics. The final argument is that a comprehensive definition, as sought by luxuology, must integrate insights from all these fields.